Prognostic value of preoperative prognostic nutritional index and its associations with systemic inflammatory response markers in patients with stage III colon cancer. Issue 1 (21st December 2017) - Peng, Jianhong; Zhang, Rongxin; Zhao, Yixin; Wu, Xiaojun; Chen, Gong; Wan, Desen; Lu, Zhenhai; Pan, Zhizhong
Abstract: Background: The prognostic nutritional index (PNI) has been widely applied for predicting survival outcomes of patients with various malignant tumors. Although a low PNI predicts poor prognosis in patients with colorectal cancer after tumor resection, the prognostic value remains unknown in patients with stage III colon cancer undergoing curative tumor resection followed by adjuvant chemotherapy. This study aimed to investigate the prognostic value of PNI in patients with stage III colon cancer. Methods: Medical records of 274 consecutive patients with stage III colon cancer undergoing curative tumor resection followed by adjuvant chemotherapy with oxaliplatin and capecitabine between December 2007 and December 2013 were reviewed. The optimal PNI cutoff value was determined using receiver operating characteristic (ROC) curve analysis. The associations of PNI with systemic inflammatory response markers, including lymphocyte‐to‐monocyte ratio (LMR), neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and C‐reactive protein (CRP) level, and clinicopathologic characteristics were assessed using the Chi square or Fisher's exact test. Correlation analysis was performed using Spearman's correlation coefficient. Disease‐free survival (DFS) and overall survival (OS) stratified by PNI were analyzed using Kaplan–Meier method and log‐rank test, and prognostic factors were identified by Cox regression analyses. Results: The preoperative PNI was positively correlated with LMR ( r = 0.483, P < 0.001) and negatively correlated with NLR ( r = − 0.441, P < 0.001), PLR ( r = − 0.607, P < 0.001), and CRP level ( r = − 0.333, P < 0.001). A low PNI (≤ 49.22) was significantly associated with short OS and DFS in patients with stage IIIC colon cancer but not in patients with stage IIIA/IIIB colon cancer. In addition, patients with a low PNI achieved a longer OS and DFS after being treated with 6–8 cycles of adjuvant chemotherapy than did those with < 6 cycles. Multivariate analyses revealed that PNI was independently associated with DFS (hazard ratios 2.001; 95% confidence interval 1.157–3.462; P = 0.013). Conclusion: The present study identified preoperative PNI as a valuable predictor for survival outcomes in patients with stage III colon cancer receiving curative tumor resection followed by adjuvant chemotherapy.